Evaluation of Students' Performance in the English Curriculum of the Bilingual Business Communication Degree - Figueroa Díaz, Jennifer Joan, (Universidad Tecnológica de Panamá, 2021)
This research studies the English Knowledge and performace of the students of the bachelor' s degree in Bilingual Business Communication of the Central Campus Victor Levvi Sasso of Universidad Tecnológica de Panamá, considering the students' performace in the sixteen courses taught in English and their experience during the career, along with the professors' perspective of the issue. In the year 2020, through the second semester was framed with descriptive and exploratory type research in a transversal design. Results of this study demonstrated that: first, the students have a perception of having the English level necessary to obtain their diploma, However, the results of the English Diagnostic Test showed the opposite; second, the professors confirmed that the students had issues to have a good performance in the courses they teach; and third, the students that enrolled in the sixth semester of the career showed in the Englih Diagnostic Test a low outcome in three out of the four skills that were studied ( writing composition, listening comprehension, and reading comprehension), and grammar and vocabulary performance.